A fully bio-based stage-evolved adhesive via supramolecular-covalent network for high-performance reed structural composites - Yuhui Huang; Meng Li; Kui Li; Yan Qing; Lei Li; Yingfeng Zuo; Yiqiang Wu (Chemical Engineering Journal, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Tanshinone IIA ameliorates pancreatic injury in type 2 diabetic mice by modulating inflammation and endoplasmic reticulum stress via the IL-6/JAK2/STAT3 pathway - Yingfeng Li; Desheng Wang; Yuhang Liu; Chenyang Liu; Meixi Chen; Jingqi Li; Zunqiu Wu; Ning Wu (Functional & Integrative Genomics, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Summer Thermal Comfort Zoning Studies of Mainland China Based on the Comprehensive Heat Index - Yingfeng Guo; Zhifeng Wu; Zihao Zheng; Xiaojun Huang; Zhongwen Hu (International Journal of Climatology, 2025)
With global warming, a better understanding of the summer thermal environment is crucial. Distinct from land surface temperature, which is the most widely noticed and employed parameter of the summer thermal environment, we constructed the Summer Comprehensive Heat Index using six common heat indices (outdoor apparent temperature, heat index, Humidex, modified discomfort index, net effective temperature, and simplified wet‐bulb global temperature) through principal component analysis, analysing its spatial distribution and temporal trends (2003–2020) at 10 km grid and county scales across mainland China. Employing Automatic Regionalisation with Initial Seed Location, Regionalisation with Dynamically Constrained Agglomerative Clustering and Partitioning, and Spatial Kluster Analysis by Tree Edge Removal regionalisation methods with spatially constrained and classical statistical approaches, a two‐tier geographical division of summer thermal comfort zones was conducted. Results indicate severe thermal stress in Southern China and the Bohai Rim regions, while regions such as the marginal region of the Tibetan Plateau, Inner Mongolia Plateau, and Yungui Plateau offer high thermal comfort, suitable for ‘sunbird’ tourism. Conversely, the Bohai Rim and lower Yangtze regions exhibit extreme heat stress with intensifying warming trends, calling for urgent adaptation. The study highlights regional thermal heterogeneity, providing insights for localised tourism planning and climate resilience strategies.

Evaluating the impacts of drilling and extraction activities on the marine carbonate system in the natural gas fields of Beibu Gulf, Northern South China Sea - Minxia Zhang; Wei Yang; Jianhang Zhang; Chuqian Lu; Yingxu Wu; Peiqiang Zhuang; Yanmei Liu; Shasha Qi; Xing Chen; Wei Deng; Zijia Zheng; Ming He; et al. (Marine Environmental Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Logic combination and diagnostic rule-based method for consistency assessment and its application to cross-sensor calibrated nighttime light image products - Zihao Zheng; Qiming Zheng; Zhifeng Wu; Zheng Cao; Hong Zhu; Yingbiao Chen; Benyan Jiang; Yingfeng Guo; Dong Xu; Francesco Marinello (Remote Sensing of Environment, 2025)

Assessment of cohesive soil landslide driving forces exerted on piles considering soil arching effects - Demin Xue; Cong Dai; Yingfeng Wu; Shuai Zhang (Engineering Geology, 2024)

Fluorescent cellulose nanofibrils-based hydrogel incorporating MIL-125-NH2 for effective adsorption and detection of iodide ion - Xuefeng Zhang; Xinmiao Qi; Jiayu Ouyang; Yingfeng Zuo; Qiang Ma; Haining Tan; Xin Guo; Yiqiang Wu (Journal of Hazardous Materials, 2024)

Achieving sustainable and highly efficient wood bonding through synergistic plant root-driven penetration mode with a hyperactive interface - Xiaoqian Bi; Yuan Zhang; Ping Li; Yan Wang; Yiqiang Wu; Yingfeng Zuo (Chemical Engineering Journal, 2024)

Degraded frozen soil and reduced frost heave in China due to climate warming - Zhongqiong Zhang; Miao Li; Zhi Wen; Zhiqiang Yin; Yingfeng Tang; Siru Gao; Qingbai Wu (Science of The Total Environment, 2023)

Molecular-level topological deep cross-fusion strategy towards organic–inorganic lightweight composites - Long Zheng; Yiqiang Wu; Xingong Li; Yingfeng Zuo (Chemical Engineering Journal, 2023)

A catastrophic rainfall-induced high landslide, occurred on December 4, 2020, in the Qingliucun mountainous area of Southwest China - Demin Xue; Cong Dai; Yingfeng Wu; Kai Chen; Jibing Tang; Shuai Zhang (Landslides, 2023)

The temporal and spatial variation of chlorophyll a concentration in the China Seas and its impact on marine fisheries - Kunlong Zhang; Xunbo Zhao; Jing Xue; Danqi Mo; Dongyu Zhang; Zhongyong Xiao; Wei Yang; Yingxu Wu; Yingfeng Chen (Frontiers in Marine Science, 2023)
Marine chlorophyll a is a key molecule for photosynthesis of marine plants and some plankton, which is important in marine ecosystems. This study utilized the chlorophyll a concentration data product observed by the MODIS sensor (MODerate resolution Imaging Spectroradiometer) to construct a long-term sequence of chlorophyll a concentration dataset by processing the raw data. Based on this, the multi-time-scale chlorophyll a concentration data was synthesized, and it was used to analyze the spatial and temporal variation characteristics of chlorophyll a concentration in China Seas. In addition, several oceanographic variables, including sea surface temperature, nutrients (phosphate, nitrate, silicate), partial pressure of seawater carbon dioxide, net primary productivity of the ocean, physical dynamics of seawater processes (mixed layer), were analyzed to ascertain their potential influence on chlorophyll a concentration. Finally, we analyzed the effects of changes in chlorophyll a concentration on marine fisheries. The result showed that: The average value of chlorophyll a concentration in China Seas from 2002 to 2022 was 0.874 mg/m 3 , with the highest concentration observed in the Bohai Sea area (4.547 mg/m 3 ) and the lowest in the South China Sea area (0.288 mg/m 3 ). The spatial variation of chlorophyll a concentration revealed an overall decrease of 0.0095 mg/m 3 in China Seas from 2002 to 2022. From the perspective of time changes, the concentration of chlorophyll a in China’s Bohai Sea area showed a downward trend from 2002 to 2022, while the Yellow Sea area showed an upward trend. The concentration remained relatively stable in the East China Sea area, whereas a significant declining trend was observed in the South China Sea area. The relationship between temperature and chlorophyll a concentration was non-linear, and chlorophyll a concentration showed some fluctuation or threshold effect with the change of seawater temperature. The three nutrient salts studied have a promoting effect on chlorophyll a, among which phosphate has the most obvious promoting effect on chlorophyll a. Chlorophyll a was negatively correlated with pCO 2 and positively correlated with ocean net primary productivity. Seasonal changes in the mixed layer had a significant effect on changes in the upper marine nutrients, which in turn affected changes in chlorophyll a concentration. Six of the eight types of algae studied show a trend toward deeper sea depths, which may have implications for the food availability of marine fish at different levels and pose new challenges for marine fisheries development.

Ring-widths of Abies at tree-line ecotone reveal three centuries of early winter season temperature changes in Yunnan, China - Yingfeng Bi; Whitney Cory; Zenxin Fan; Jingchao Yang; Zhikun Wu; Wei Huang; Jianwen Li; Xuefei Yang (Climate Dynamics, 2020)
Variation in winter temperature is less well understood than in annual and summer temperatures over long timescales, particularly in low-latitude (0–30° N) montane regions with large spatial and topographic heterogeneity. Understanding these variations could be critical for forest manageemnt in these important tree growing regions. We collected tree-ring cores from Yunnan Province in montane southwest China, to determine how winter temperature has varied in the past and to explore its possible drivers in this region. Six highly correlated site chronologies were combined into a long and well-replicated regional composite (RC) chronology. The RC chronology correlated strongest with mean early winter season temperature (EWST) from November to January during 1959–2015. We applied RC chronology to reconstruct EWST from 1653 to 2015. The reconstruction shows five relatively warm historic intervals (1658–1718, 1743–1755, 1771–1791, 1929–1959, and 1995–2015) and cold intervals (1720–1742, 1792–1852, 1860–1883, 1905–1928, and 1960–1994). The 1950s with six anomalous warm seasons and 1980s with five anomalous cold seasons were the warmest and coldest decades, respectively. The EWST reconstruction generally agreed with other winter temperature reconstructions from nearby areas and with historical documents. Atlantic Multidecadal Oscillation (AMO) might be a key forcing of multidecadal winter temperature variations in montane southwest China over the past three and half centuries. Both warm and cold temperature periods coincide with respective positive and negative phases of AMO. Besides, the cold intervals during the nineteenth and twentieth centuries may also have been influenced by large volcano eruptions in low-latitude regions of south and east Asia. Our EWST reconstruction not only improves our understanding of the trends and variations of winter climate history, but also supports planning for resilience in conservation, agriculture, and forestry management in montane southwest China into the future.

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)

A method suitable for DNA extraction from humus-rich soil - Tianjin Miao; Song Gao; Shengwei Jiang; Guoshi Kan; Pengju Liu; Xianming Wu; Yingfeng An; Shuo Yao (Biotechnology Letters, 2014)

A convenient colony-based transformation method for high-throughput changing of plasmid hosts - Yingfeng An; Anguo Lv; Wenfang Wu (Biotechnology Letters, 2010)

Random mutagenesis and recombination of sam1 gene by integrating error-prone PCR with staggered extension process - Yingfeng An; Jianfei Ji; Wenfang Wu; Ribo Huang; Yutuo Wei; Zhilong Xiu (Biotechnology Letters, 2008)